2017
DOI: 10.1016/j.rbmo.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tissue cryopreservation in female-to-male transgender people: insights into ovarian histology and physiology after prolonged androgen treatment

Abstract: Female-to-male transgender people (trans men) are faced with the risk of losing their reproductive potential owing to gender-affirming hormone treatment and genital reconstructive surgery. This observational, prospective cohort study investigates the effect of prolonged androgen therapy on their ovarian histology and fertility preservation perspectives. Hormone serum levels, ovarian histology and cumulus-oocyte complexes (COC) of 40 trans men were analysed at the moment of hysterectomy with bilateral oophorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 27 publications
13
86
3
1
Order By: Relevance
“…Typically, GRPs are young and have a high follicle density. Although all GRPs undergo androgen-therapy prior to oophorectomy, their follicles do not differ in distribution, number and quality from untreated women [23], and they can achieve pregnancy after discontinued hormone treatment [24]. In support of this, our data show that ovaries from GRPs have the same cell composition as tissue from C-sec patients.…”
Section: Discussionsupporting
confidence: 67%
“…Typically, GRPs are young and have a high follicle density. Although all GRPs undergo androgen-therapy prior to oophorectomy, their follicles do not differ in distribution, number and quality from untreated women [23], and they can achieve pregnancy after discontinued hormone treatment [24]. In support of this, our data show that ovaries from GRPs have the same cell composition as tissue from C-sec patients.…”
Section: Discussionsupporting
confidence: 67%
“…Androgen excess is a key trait in the majority (~60%) of women with PCOS, and the most frequent common feature, as hyperandrogenism is a diagnostic criteria in three out of the four PCOS phenotypes (A-D) endorsed by the 2018 international evidence-based guidelines (Livadas et al 2014, Teede et al 2018. Interestingly, the presence of elevated androgen levels observed in congenital adrenal hyperplasia patients (Lucis et al 1966, Hague et al 1990 and female-to-male transsexuals treated with testosterone (Futterweit & Deligdisch 1986, Spinder et al 1989, De Roo et al 2017 are reported to cause the appearance of polycystic ovarian morphology (PCOM), similar to that observed in women with PCOS, with enlarged ovaries that exhibit multiple cysts and theca interstitial hyperplasia. Serum levels of testosterone, A4 and DHEAS, and the enzyme required to transform pro-androgens to bioactive androgens -3β-hydroxysteroid dehydrogenase (3β-HSD)have all been reported to be elevated in hyperandrogenic PCOS women (Keefe et al 2014, Palomba et al 2014, O'Reilly et al 2017.…”
Section: Clinical Evidence Supporting a Role For Androgens In Drivingmentioning
confidence: 99%
“…In transsexual patients, the ovaries show similar numbers of primordial and primary follicles in the ovarian cortex as compared with healthy females of the same age (De Roo et al, ). Thus, primordial follicles are not depleted from the ovarian cortex of transsexual females after treatment with testosterone (Van den Broekcke et al, ).…”
Section: Introductionmentioning
confidence: 99%